The concept of micro toponyms. Study of micro toponyms - Torayeva Sayyora Bakhtyorovna; Mohiba Kargar; Hilala Nuri (Zien Journals, 2023)
This article talks about the concept of microtoponyms and researches on microtoponyms.
Keywords: microtoponym; ethnic name; ethnotoponym; anthrotoponym